Regionalism and Migration Governance: The Institutional Role of ASEAN in Complementary Pathways for Labour Mobility - Amri, Aqmal Reza; Muliastuti, A. (Kybernology : Journal of Government Studies, 2025)
This paper examines the institutional role of ASEAN in developing complementary pathways for labour mobility in Southeast Asia. Moving beyond normative debates on ASEAN’s relevance as a regional institution, the study explores how the region’s distinctive institutional design, grounded in state sovereignty, non-interference, and consensus, shapes migration governance. Using a qualitative approach, this study draws on ASEAN policy documents, national labour regulations, and reports from international organisations such as the IOM, ILO, and UNHCR. Findings show that ASEAN’s complementary pathways are primarily realised through temporary labour schemes, bilateral agreements, and regional normative frameworks such as the 2007 ASEAN Declaration and the 2017 ASEAN Consensus on the Protection and Promotion of the Rights of Migrant Workers. While these instruments provide an important normative foundation, their soft law status results in uneven implementation and heavy reliance on national political commitment. The high proportion of undocumented migrant workers and fragmented protection mechanisms underscore the limitations of ASEAN’s consensus-based, intergovernmental model. The study highlights the dual role of complementary pathways as both a bridge between labour market demands and migrant rights protection and as a reflection of ASEAN’s institutional constraints. It argues that strengthening these pathways requires expanding regional coordination, integrating international labour standards, and positioning rights protection as a central pillar of migration governance rather than as an adjunct to labour mobility. By comparing ASEAN with the European Union’s more integrated model, the paper underscores ASEAN’s potential to develop a flexible, inclusive, and progressively rights-based approach suited to the political and economic realities of the Global South.